Firewall guidelines and policies - Ávila, Álex; Echeverría Jiménez, Tatiana; Obando, Christian; Ortiz Zuleta, Carlos Federico; Ávila, Álex; Echeverría Jiménez, Tatiana; Obando, Christian; Ortiz Zuleta, Carlos Federico (Corporación universitaria Americana, 2022)
Information systems must be protected by firewalls, which are designed to control traffic flowing between private andpublic networks, allowing and denying requests made by the different networks in order to protect them from threats. Thereare different types of firewalls that are used depending on the filtering techniques to be implemented, according to the TCP/IP protocol stack, they can work at network, transport and application level. A good firewall policy design strengthensnetwork security by controlling certain types of data traffic.